Pengembangan lembar aktivitas siswa (LAS) matematika berbasis penemuan terbimbing untuk kelas VII Sekolah Menengah Pertama pada materi bentuk aljabar - Riarti, Mimi; Ario, Marfi; Isharyadi, Ratri (Karoteh Utama, 2021)
This study aims to develop a Guided Discovery-based Student Activity Sheet for seventh-grade students in junior high school, focusing on Algebraic Form material and ensuring its validity. The research follows the Research and Development method, consisting of three main stages: defining, designing, and developing. The instrument used in this study is a validation questionnaire. Based on the validity test of the Guided Discovery-based Student Activity Sheet conducted by two validators with several revisions and improvements, the average validation score obtained was 3.03, indicating a highly valid category. Thus, the Guided Discovery-based Student Activity Sheet for Algebraic Form material, intended for seventh-grade students in junior high school, is valid.